The Histone H3K27me3 Demethylases KDM6A/B Resist Anoikis and Transcriptionally Regulate Stemness-Related Genes - Shait Mohammed, Mohammed Razeeth; Zamzami, Mazin; Choudhry, Hani; Ahmed, Firoz; Ateeq, Bushra; Khan, Mohammad Imran (Frontiers in Cell and Developmental Biology, 2022)
Epithelial cancer cells that lose attachment from extracellular matrix (ECM) to seed in a distant organ often undergo a specialized form of apoptosis called anoikis. Recently KDM3A (H3K9 demethylase) is identified as a critical effector of anoikis in cancer cells. But whether other histone demethylases are involved in promoting or resisting anoikis, is still remains elusive. We screened the major histone demethylases and found that both H3K27 histone demethylases namely KDM6A/B were highly expressed during ECM detachment. Inhibition of KDM6A/B activity by using a specific inhibitor results in reduced spheres formation capacity and increased apoptosis. Knockout of KDM6B loss the stem cell properties in detached cells, Further, we found that KDM6B maintains stemness by transcriptionally regulating the expression of stemness genes SOX-2, SOX-9, and CD44 in detached cells. KDM6B occupies the promoter region of both SOX-2 and CD44 to regulate their expression epigenetically. We also noticed increased occupancy of HIF1α promoter by KDM6B, suggesting its regulatory role in maintaining hypoxia in detached cancer cells. This observation was further strengthened as we found a significant positive association in the expression of both KDM6B and HIF1α in various cancer types. Overall, our results presented here reveals a novel transcriptional program that regulates resistance against anoikis and maintains stemness-like properties.